2016
DOI: 10.1371/journal.pone.0153939
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Possibility of Using Peptides with a Helical Repeating Pattern of Hydro-Phobic and Hydrophilic Residues to Inhibit IL-10

Abstract: Blockade of IL-10 signalling clears chronic viral and bacterial infections. Immunization together with blockade of IL-10 signalling or relatively low level of IL-10 further enhances viral and bacterial clearance. IL-10 functions through binding to interleukin 10 receptor (IL-10R). Here we showed that peptides P1 and P2 with the hydrophobic and hydrophilic pattern of the IL10R-binding helix in IL-10 could bind with either IL-10R1 or IL-10, and inhibit inflammatory signals with long duration and negligible cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In a previous study, 1 it was shown that P1 and P2 compete with IL-10 in binding with IL-10R1 (Fig. S2).…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…In a previous study, 1 it was shown that P1 and P2 compete with IL-10 in binding with IL-10R1 (Fig. S2).…”
Section: Resultsmentioning
confidence: 70%
“…1 No multiplycharged adduct peaks, formed between P1/P2 and IL-10R1, were detected using MALDI mass spectrometry, and no corresponding peak was identified in the case of P3 (negative control). Thus, to further study the potential for the interplay of bioactive peptides P1 and P2 with IL-10R1, molecular dynamics (MD) simulation was used to model the complexes formed, and compared to the negative control peptide P3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations